A Broad‐High Temperature Ceramic Capacitor with Local Polymorphic Heterogeneous Structures - Binglong Zheng; Ying Lin; Haibo Yang; Hongmei Jing; Hu Nan; Yifei Wang; Fang‐Zhou Yao; Minquan Wang; Qibin Yuan (Advanced Science, 2025)
Abstract Crafting high‐performance dielectrics tailored for pulsed power capacitors, in response to the escalating demands of practical applications, presents a formidable challenge. Herein, this work introduces a novel lineup of lead‐free ceramics with local polymorphic heterogeneous structures, defined by the formula (1‐x)[0.92BaTiO3‐0.08Sr(Mg1/2Ti3/4)O3]‐x(Na0.5Bi0.5)TiO3 (BT‐SMT‐xNBT). This innovative multi‐scale synergistic strategy, spanning from the atomic to grain scale, yields materials with a giant recoverable energy density (Wrec) of 10.1 J·cm−3 and an impressive energy efficiency (η) of 95.0%. The integration of linear end elements SMT can significantly mitigate the polarization hysteresis while concurrently boosting the breakdown strength, thus enhancing overall energy efficiency. Furthermore, the inclusion of NBT with high polarization serves to amplify domain size, thereby reinforcing the electric field‐induced polarization. This addition also stimulates the creation of polymorphic heterostructures, where tetragonal and rhombohedral nanodomains coexist, as validated by aberration‐corrected transmission electron microscopy. Notably, the BT‐SMT‐0.2NBT ceramics have demonstrated outstanding high‐temperature energy storage capabilities, with a Wrec of 7.2 J·cm−3 and an η of 92.2% at 150 °C, along with remarkable broad‐temperature stability (ΔWrec, Δη ≤ 4.0%, ≈20–150 °C). These achievements in this work propel the field toward more practical and durable solutions of energy storage dielectrics.